2010
DOI: 10.1103/physrevb.82.165115
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and impurity-induced emission bands inSrHfO3

Abstract: To better understand the scintillation mechanism in SrHfO 3-based scintillators we investigate in detail their x-ray excited radioluminescence ͑RL͒ emissions. The Gaussian decomposition of the undoped SrHfO 3 RL spectra manifests the presence of four emission bands peaking at 3.0, 4.0, 4.6, and 5.1 eV. Based on corresponding photoluminescence emission and excitation spectra we tentatively associate the observed bands with excitonic or defect-related emissions. When doped by Ce 3+ or Pb 2+ luminescent activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Ce 3+ emission intensity increases up to Ce0.1 sample. The origin of the 335 nm band is in question as it has not been observed in the stoichiometric undoped SHO [12]. Its spectral position is very close to that of Pb 2+ center [10,11], but contamination by Pb ions is practically excluded in these samples (checked by ICP analysis).…”
Section: Heavily Ce-doped Srhfomentioning
confidence: 97%
See 1 more Smart Citation
“…Ce 3+ emission intensity increases up to Ce0.1 sample. The origin of the 335 nm band is in question as it has not been observed in the stoichiometric undoped SHO [12]. Its spectral position is very close to that of Pb 2+ center [10,11], but contamination by Pb ions is practically excluded in these samples (checked by ICP analysis).…”
Section: Heavily Ce-doped Srhfomentioning
confidence: 97%
“…Very recently the systematic study of the excitation and emission characteristics in the undoped stoichiometric SHO has been performed [12] which reveals quite several UV-VIS emissions ascribed to the exciton and defect centers. In the Pb or Ce-doped SHO the competition between these ''intrinsic'' centers and the dopants was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it may be concluded that these peaks follow first order recombination kinetics [12]. The contour plot displayed in Figure 2 shows the presence of a prominent emission due to Ce 3+ ion at around 400 nm [6,13] accompanied by a weak defect emission at higher wavelength.…”
Section: Study Of the Trapping States By Tslmentioning
confidence: 99%
“…On the other hand, in this case the distortion of the temperature dependence of the PL intensity could occur due to the energy losses in the process of transfer between the host and the Ce 3+ center. Nevertheless, PLE spectra of SHO:Ce 3+ measured in the VUV region [13] showed rather efficient energy transfer between the SHO host and the Ce 3+ ion. PLE spectra at RT (see Figure 4) show in great detail that the transfer of excitation from the host to the Ce 3+ luminescence ion is not only efficient but also fast.…”
Section: Correction For the Temperature Quenching Of The Ce 3+ Emissimentioning
confidence: 99%
See 1 more Smart Citation